2020
DOI: 10.22373/crc.v4i2.6660
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Multimedia Interaktif Power Point Pada Mata Diklat Dasar Dan Pengukuran Listrik

Abstract: The purpose of this study is to seek to improve the learning outcomes of students using interactive multimedia Power Point work on the subjects of Basic learning and Electrical Measurements Work in class X TIPTL 2 SMKN 1 Padang. This type of study is a quasi-experiment. Students of class X TITL 2 Padang 1 SMKN were collected in the 2016/2017 school year consisting of 30 students as research subjects. Collecting data in this study using the test results to learn pre and post objective be about 30 items to 30 it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 5 publications
0
3
0
14
Order By: Relevance
“…χ 2 count ≥ χ 2 table , meaning that the data distribution is not normal. With a significant level = 0.05 and degrees of freedom (dk) = k -1 [15]. From the results of the calculation of the normality test of the experimental class and control class data, it can be concluded that the data has met the normality test criteria with the results of the experimental class posttest data being 5,99 ≤ 9,49 and for the control class posttest data is 2,28 ≤ 9,49 this means that the data of the two samples is normal.…”
Section: Data Analysis 1 Normality Testmentioning
confidence: 99%
“…χ 2 count ≥ χ 2 table , meaning that the data distribution is not normal. With a significant level = 0.05 and degrees of freedom (dk) = k -1 [15]. From the results of the calculation of the normality test of the experimental class and control class data, it can be concluded that the data has met the normality test criteria with the results of the experimental class posttest data being 5,99 ≤ 9,49 and for the control class posttest data is 2,28 ≤ 9,49 this means that the data of the two samples is normal.…”
Section: Data Analysis 1 Normality Testmentioning
confidence: 99%
“…1) Uji Normalitas Bertujuan untuk menentukan sebaran data yang diperoleh berdistribusi normal atau tidak, apabila sebaran data berdistribusi normal maka uji hipotesis dapat dilakukan, data berdistribusi normal apabila angka signifikan yang dihasilkan lebih besar dari 0,05. Uji Normalitas dilakukan menggunakan rumus Chi-Square [20], dengan kriteria pengujian normalitas yaitu jika χ 2 hitung ≥ χ 2 tabel, artinya distribusi data tidak normal. Jika χ 2 hitung ≤ χ 2 tabel, artinya data berdiasi normal dengan taraf signifikan = 0,05 dan derajat kebebasan (dk) = k -1.…”
Section: Teknik Analisis Dataunclassified
“…2) Uji Homogenitas Uji homogenitas bertujuan untuk mengukur apakah sebuah kelas mempunyai varians yang sama diantara kelas eksperimen dan kelas kontrol, data yang memiliki varians yang sama apabila angka siqnifikan yang dihasilkan lebih besar dari 0,05. Uji homogenitas untuk kedua kelas diukur dengan menggunakan Uji F [20]. Dengan kriteria pengujian homogenitas yaitu jika Fhitung < Ftabel, artinya data mempunyai varians yang homogen.…”
Section: Teknik Analisis Dataunclassified
See 1 more Smart Citation
“…One of the innovations that can be applied to online learning is the use of learning media (Laila, Hb, & Irsadi, 2016). The use of learning media can increase the motivation and interest of students if the media used can provide stimulation to students in the learning process (Candra, Elfizon, Islami, & Yanto, 2020;Hutabri & Putri, 2019;Zaus, Wulansari, Islami, & Pernanda, 2018). Multimedia is defined as a computer program consisting of text, graphics, sound and images and animation.…”
Section: ▪ Introductionmentioning
confidence: 99%